ChemInform Abstract: Driving the Morita—Baylis—Hillman Reaction to a Multicomponent Organic Transformation. Issue 43 (21st October 2014) - Guillouzic, Anne‐Francoise; Montel, Sonia; Laborde, Coralie; Volle, Jean‐Noel; Pirat, Jean‐Luc; Virieux, David
Abstract It is demonstrated, that employing heterophosphines under aqueous Morita—Baylis—Hillman conditions changes the course of the reaction to provide hydrolysis products of type (IV), (VI), and (VIII).